Governing equations of RBS-DEM elements small displacements formulation - Guan, Paul Bryan L.; Tingatinga, Eric Augustus J.; Longalong, Romeo Eliezer U. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
Rigid Body Spring - Discrete Element Method (RBS-DEM) is a simple alternative to the Finite Element Method that can be used to model structural elements. Numerical methods had been used to determine the response through RBS-DEM models subjected to applied loads. In this study, the closed form analytical solution of the RBS-DEM model is investigated as it can serve as an alternative method for validating a proposed RBS-DEM model. The main objective of this study is to derive the governing equations of RBS-DEM planar elements subjected to lateral loads and horizontal ground motion. The governing equations of the model undergoing large displacements will be derived using D'Alembert's principle and will be linearized to obtain the corresponding small displacement formulation. The derived equations were implemented in a program to simulate the response of a reinforced concrete column. The parameters of the springs were obtained using Response2000 software and hysteresis models were used and the response of the models were compared to the experimental results from PEER. Comparisons show that the one-component models were able to simulate the elastic stiffness reasonably but underestimates the displacement capacity of actual colwnns. As expected, the multi-component model provided more flexibility to the model but this study recommends more detailed review and validation of the nonlinear parameters of the springs to be used.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Structural analysis (Engineering); Discrete element method